2016
DOI: 10.1136/bjophthalmol-2016-308807
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of keratoplasty in the mucopolysaccharidoses: an international perspective

Abstract: Clear corneal grafts can be obtained for patients with corneal clouding due to mucopolysaccharidosis with improvement in visual acuity in the majority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
6

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 22 publications
0
28
0
6
Order By: Relevance
“…A very recent study by many authors [ 31 ] carried out a comprehensive review of keratoplasty in 32 patients from seven countries (Brazil, England, Finland, Germany, Portugal, Sweden, and USA; 16 bilateral and 16 monolateral) found that PKP was performed in 45 of the cases while DALK was only performed in three; at the last follow-up, successful results were reported in 63% of the first/only operated eye. Rejection episodes occurred in 23% of grafts.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study by many authors [ 31 ] carried out a comprehensive review of keratoplasty in 32 patients from seven countries (Brazil, England, Finland, Germany, Portugal, Sweden, and USA; 16 bilateral and 16 monolateral) found that PKP was performed in 45 of the cases while DALK was only performed in three; at the last follow-up, successful results were reported in 63% of the first/only operated eye. Rejection episodes occurred in 23% of grafts.…”
Section: Introductionmentioning
confidence: 99%
“…Clear corneal grafts can be achieved for patients with MPS VI who have corneal clouding, and may result in improvements in visual acuity [105]. Rejection episodes have been reported following corneal transplantation in patients with MPS VI; however, it should be noted that most occurred in those who were transplanted at a younger age (13–28 years old) [105, 106]. Generally, the recurrence of corneal deposits has not been reported in patients with MPS VI [105, 106].…”
Section: Resultsmentioning
confidence: 99%
“…The choice of surgical technique for corneal transplantation (deep anterior lamellar keratoplasty [DALK] or penetrating keratoplasty [PK]) should be made on a case-by-case basis. There is some evidence from the general population to suggest that rejection is more likely to occur following PK than DALK [106108]; as such, DALK should be considered as the first approach in patients with MPS VI.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, one of our patients was referred for surgical corneal intervention, but chose to postpone surgery as the binocular visual acuity at that time was still 0.3. Although penetrating keratoplasty has been reported to be successful , there is a risk of re‐accumulation of glucoseaminoglycans in the donor keratocytes . Studies have showed successful outcomes with deep anterior lamellar keratoplasty in children with MPS .…”
Section: Discussionmentioning
confidence: 99%